2017
DOI: 10.1016/j.geomorph.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Speleogenesis, geometry, and topology of caves: A quantitative study of 3D karst conduits

Abstract: International audienceKarst systems are hierarchically spatially organized three-dimensional (3D) networks of conduits behaving as drains for groundwater flow. Recently, geostatistical approaches proposed to generate karst networks from data and parameters stemming from analogous observed karst features. Other studies have qualitatively highlighted relationships between speleogenetic processes and cave patterns. However, few studies have been performed to quantitatively define these relationships. This paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…The mean flow section along the tracer transport is about 9 m 2 , the mean flow velocity is 0.16 m/s and the mean length of the conduits between injection and recovery point was about 905 m. Dividing the length of the total conduits by the apparent distance between injection and recovery point gives and estimation of tortuosity. In karst systems, the tortuosity generally varies from 1.10 to 1.40 depending on the morphology of the conduit networks [70]. Considering an apparent distance of 850 m between injection and recovery sites [13], the mean tortuosity here is about 1.06, getting closer to the range of value for an angular maze conduit network morphology [70].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The mean flow section along the tracer transport is about 9 m 2 , the mean flow velocity is 0.16 m/s and the mean length of the conduits between injection and recovery point was about 905 m. Dividing the length of the total conduits by the apparent distance between injection and recovery point gives and estimation of tortuosity. In karst systems, the tortuosity generally varies from 1.10 to 1.40 depending on the morphology of the conduit networks [70]. Considering an apparent distance of 850 m between injection and recovery sites [13], the mean tortuosity here is about 1.06, getting closer to the range of value for an angular maze conduit network morphology [70].…”
Section: Discussionmentioning
confidence: 76%
“…In karst systems, the tortuosity generally varies from 1.10 to 1.40 depending on the morphology of the conduit networks [70]. Considering an apparent distance of 850 m between injection and recovery sites [13], the mean tortuosity here is about 1.06, getting closer to the range of value for an angular maze conduit network morphology [70]. The variability of the mean flow section along the transport and the length of transport appears to be lower than for the mean flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…The topology of karst conduits has been strongly linked to their spatial location and the governing flow characteristics (e.g., Audra & Palmer, 2015; Gabrov et al, 2014; Palmer, 1992). For example, anastomosic caves, defined by their braided patterns, typically occur across bedding planes in the epiphreatic zone, whereas angular mazes tend to be associated with fractured media due to seepage from overlying insoluble rocks (Jouves et al, 2017). While near‐surface features such as flank margin caves (Mylroie et al, 1990) can be observed in many coastal carbonate environments along the salt‐freshwater mixing zone, limited accessibility has prevented large‐scale speleological surveys of karst conduits in coastal aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…Karst aquifers also have a peculiar hydrodynamic functioning due to large and permeable conduits, related to the speleogenetic history of the carbonate rocks (Jouves et al 2017). Groundwater flows through the karst network and converges to the springs that concentrate the water discharge in few outlets.…”
Section: Introductionmentioning
confidence: 99%